MONOGAMI PENDEKATAN TEOLOGI DALAM SURAH AN-NISA’ AYAT 129 - Hilmi Asrori; Ahmad Arifi (LPPM STAI Ihyaul Ulum Gresik, 2026)
This study aims to reveal the concept of monogamy from an Islamic theological perspective by focusing on Surah An Nisa’ verse 129. Although the Qur’an in other verses provides space for the practice of polygamy, this verse contains nuances that emphasize the justice and welfare of wives, which implicitly limits the choice of polygamy and affirms monogamy as the main moral attitude. This research method uses a qualitative library approach, with textual analysis techniques on Qur’anic manuscripts and classical-modern interpretations (Al Thabari, Al Qurtubi, Ibn Kathir, to Sayyid Qutb), as well as contemporary fiqh studies to contextualize the results of the interpretation. The findings show that the theology of monogamy in verse 129 is seen from the emphasis on the husband’s responsibility in fulfilling the emotional, material, and spiritual rights of the wife, as well as the obligation to uphold justice which is often difficult to fulfill in polygamy. Thus, although polygamy is permitted, the Qur’an encourages people to make monogamy the main choice in order to realize a harmonious and just family.